SIGN OF MOTHERHOOD AND MONSTROSITY IN BLOOD RED SKY MOVIE - Sita Aprilia; Fitriyani Bakri; Yunitari Mustikawati (Faculty of Languages and Literature, Universitas Negeri Makassar, 2026)
Film functions as a powerful cultural medium that communicates social values, identities, and ideologies through visual and narrative signs, making it an important site for examining representations of gender and motherhood in contemporary cinema. While previous studies on horror films have largely discussed maternal figures from feminist perspectives or idealized constructions of motherhood, less attention has been paid to the symbolic and ideological meanings that emerge when maternal identity intersects with monstrosity. This study analyzes how motherhood and monstrosity are constructed and interconnected in the character of Nadja in Blood Red Sky (2021) by applying Roland Barthes’s semiotic theory of denotation, connotation, and myth. We employed a qualitative descriptive method with purposive sampling, and examined selected key scenes through visual and narrative signs such as color symbolism, lighting, facial expressions, body movement, and cinematographic techniques. The findings show that motherhood is represented through emotional care, moral responsibility, and ultimate sacrifice, while monstrosity is framed as a transformative process driven by maternal necessity rather than as a purely destructive force. At the mythic level, the film naturalizes the ideology that maternal love can legitimize transformation, violence, and self-sacrifice, positioning the maternal body as a space where vulnerability and power coexist. This study offers a novel contribution by demonstrating that monstrosity in Blood Red Sky is not opposed to motherhood but becomes an integral part of it. These findings are significant for literary and film studies because they expand semiotic and feminist readings of maternal figures, showing how contemporary narratives reinterpret motherhood as a complex, ambivalent, and ideologically negotiated identity rather than a fixed or purely nurturing role.